Identification of CD5/Cyclin D1 Double-negative Pleomorphic Mantle Cell Lymphoma: A Clinicopathologic, Genetic, and Gene Expression Study. (February 2020) - Chuang, Wen-Yu; Chang, Sheng-Tsung; Yuan, Chang-Tsu; Chang, Gwo-Jyh; Chang, Hung; Yeh, Chi-Ju; Ueng, Shir-Hwa; Kao, Hsiao-Wen; Wang, Tong-Hong; Wan, Yung-Liang; Shih, Lee-Yung; Chuang, Shih-Sung; et al.
Abstract : Pleomorphic mantle cell lymphoma (PMCL) can closely mimic diffuse large B-cell lymphoma (DLBCL) morphologically, and expression of CD5 and cyclin D1 is helpful for differential diagnosis. To date, no cases of CD5/cyclin D1 double-negative PMCL have been reported. Four cases of B-cell lymphoma with an immunophenotype of CD5(−) cyclin D1(−) SOX11(+) and morphologic features compatible with DLBCL were included. Two were previously identified, and the other 2 were screened from 500 cases of B-cell lymphoma. We analyzed their clinicopathologic, immunophenotypic, genetic, and gene expression features. Cases of cyclin D1-positive PMCL, cyclin D1-negative PMCL, germinal center B-cell (GCB) DLBCL, and activated B cell (ABC) DLBCL were also studied for comparison. Similar to other PMCL cases, these 4 patients were mainly elderly male individuals with an aggressive clinical course. None of these tumors had detectable translocations involving CCND1, CCND2, CCND3, CCNE1, CCNE2, MYC, BCL2, or BCL6 . The genome-wide copy number profile of these 4 cases was similar to that of cyclin D1-negative PMCL. None of these tumors had high expression of cyclin D1, cyclin D2, or cyclin D3. Similar to cyclin D1-negative PMCL, these cases had higher expression of cyclin E1 and cyclin E2 compared with cyclin D1-positive PMCL. The gene expression pattern of these tumors was also similar to that of cyclin D1-negative PMCL. Here we report for the first time 4 cases of CD5/cyclin D1 double-negative PMCL. SOX11 positivity is useful to identify these rare tumors, and further genetic and gene expression analysis can be used to confirm the diagnosis.